CRISPR/dCas9-Mediated DNA Methylation Editing on emx2 in Chinese Tongue Sole (Cynoglossus semilaevis) Testis Cells - Sun, Yanxu; Wang, Hong-Yan; Liu, Binghua; Yue, Bowen; Liu, Qian; Liu, Yuyan; Rosa, Ivana F. [UNESP]; Doretto, Lucas B.; Han, Shenglei; Lin, Lei; Gong, Xiaoling; Shao, Changwei (MDPI, 2024)
DNA methylation is a key epigenetic mechanism orchestrating gene expression networks in many biological processes. Nonetheless, studying the role of specific gene methylation events in fish faces challenges. In this study, we validate the regulation of DNA methylation on empty spiracles homeobox 2 (emx2) expression with decitabine treatment in Chinese tongue sole testis cells. We used the emx2 gene as the target gene and developed a new DNA methylation editing system by fusing dnmt3a with catalytic dead Cas9 (dCas9) and demonstrated its ability for sequence-specific DNA methylation editing. Results revealed that utilizing dCas9-dnmt3a to target emx2 promoter region led to increased DNA methylation levels and decreased emx2 expression in Chinese tongue sole testis cells. More importantly, the DNA methylation editing significantly suppressed the expression of MYC proto-oncogene, bHLH transcription factor (myc), one target gene of emx2. Furthermore, we assessed the off-target effects of dCas9-dnmt3a and confirmed no significant impact on the predicted off-target gene expression. Taken together, we developed the first DNA methylation editing system in marine species and demonstrated its effective editing ability in Chinese tongue sole cells. This provides a new strategy for both epigenetic research and molecular breeding of marine species.
Keywords: CRISPR/dCas9; Cynoglossus semilaevis; DNA methylation; emx2